For Slavery and Union : Benjamin Buckner and Kentucky Loyalties in the Civil War - Lewis, Patrick A., 1984- (Book collections on Project MUSE., 2015)
Benjamin Forsythe Buckner (1836--1901) faced a dire choice as the flames of Civil War threatened his native Kentucky. As an ambitious Bluegrass aristocrat, he was sympathetic to fellow slave owners, but was also convinced that the Peculiar Institution could not survive a war for Southern independence. Defying the wishes of his Rebel fiancee and her powerful family -- yet still hoping to impress them with his resolve, independence, and courage -- Buckner joined the Twentieth Kentucky Volunteer Infantry in 1861 as a Union soldier. President Abraham Lincoln's issuance of the Emancipation Proclama.